New-Firm Survival and the Technological Regime - Audretsch, David B. (The Review of Economics and Statistics, 1991)
The survival rates of over 11, 000 firms established in 1976 are compared across manufacturing industries. The variation in ten-year survival rates across industries is hypothesized to be the result of differences in the underlying technological regime and industry-specific characteristics, especially the extent of scale economies and capital intensity. Based on 295 four-digit standard industrial classification industries, new-firm survival is found to be promoted by the extent of small-firm innovative activity. The existence of substantial scale economies and a high capital-labor ratio tends to lower the likelihood of firm survival. However, these results apparently vary considerably with the time interval considered. Market concentration is found to promote short-run survival, while it has no impact on long-run survival. Copyright 1991 by MIT Press.